Shaposhnikov Alexander Konstantinovich: life in science and creativity - Buribayeva, Майнура; Amanzholova, Джемма; Shaimerdenova, Нурсулу (Turkic Studies Journal, 2022)
Summary of the publication. The article is dedicated to the memory of Alexander Konstantinovich Shaposhnikov, Candidate of Philological Sciences, Doctor of Philosophy (PhD), researcher of the Department of Etymology and Onomastics of the V.V. Vinogradov Institute of the Russian Language of the Russian Academy of Sciences. As a student of Ninel Zeynalovna Gadzhieva, he received her advice in the field of comparative studies, Turkology and Altaic studies, which were later embodied in the candidate’s thesis of A.K. Shaposhnikov, as well as in many research works. Later, his supervisor was an outstanding researcher, academician Oleg Nikolaevich Trubachev. The talented student of the academician continued the research of his teacher and became a famous lexicographer, etymologist, author and compiler of a number of academic, popular academic works and translations. The topic of the candidate’s dissertation «The experience of reconstruction of the relic language (based on materials related to the Khazar Khaganate)» was carried out under the supervision of N.G. Gadzhieva and O.N. Trubachev in 1992. This research direction became the starting point in all the further activities of A.K. Shaposhnikov, defining the scope of his scientific interests related to historical lexicography, etymology, ancient onomastics, mythology, as well as translations of ancient texts (from ancient Greek, Latin). For several years, he was the head of the annual readings in memory of Academician of the Russian Academy of Sciences O.N. Trubachev from the cycle «Northern Black Sea Region: to the origins of Slavic culture». A.K. Shaposhnikov has repeatedly visited Kazakhstan and participated in linguistic forums, closely cooperated with Kazakh researchers engaged in etymological research, Turkic-Slavic language contacts, the language of monuments of Russian writing of various periods, and, most importantly, lectured and participated in a joint (with Kazakh researchers) international project on the lexicographic description of Turkisms in Slavic languages in 2013-2014. A.K. Shaposhnikov together with Kazakh researchers worked on the project «Corpus of Turkic language units in East Slavic languages: ways of penetration and adaptation», the purpose of which was a comprehensive synchronic and diachronic study of the features of semantics and functioning of Turkisms in heterogeneous and homogeneous languages, followed by the compilation of a Dictionary of Turkisms. Alexander Konstantinovich Shaposhnikov died from complications caused by viral pneumonia on July 7, 2021, leaving behind numerous studies in the field of lexicography, etymology and onomastics.